IMPLEMENTASI KODE ETIK DALAM PRAKTIK PEMBELAJARAN PENDIDIKAN AGAMA KRISTEN - Angguini, Mispa; Malelak, Difly Praise (Metanoia, 2024)
The code of ethics is a guideline for teachers to act professionally and responsibly in carrying out their duties as teachers in educating their students. The purpose of this study is to find out the code of ethics in teaching in delivering material and we know the obstacles for students in ongoing learning. Qualitative methods are used by collecting data from various sources, then developed as part of data analysis. The teacher's code of ethics is the main moral foundation in the teacher's union in carrying out their duties as educators, directing, guiding professionals for their students.